2014
DOI: 10.1002/ana.24159
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 2/4 heterodimer mediates inflammatory injury in intracerebral hemorrhage

Abstract: Our results suggest that a novel TLR2/TLR4 heterodimer induced by Hb initiates inflammatory injury in ICH. Interfering with the assembly of the TLR2/TLR4 heterodimer may be a novel target for developing effective treatment of ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 33 publications
2
141
0
Order By: Relevance
“…These specific genes function in efferocytosis and in the inhibition of cytokine responses (Axl), phagolysosome formation (Lamp1 and Cd63) and lipid efflux (Abcg1) (41,42). Clustering very closely were bin and TLR4 activation are critical initiators of the inflammatory response after ICH (30,(46)(47)(48)(49)(50)(51). After stimulation, bone marrowderived macrophages (BMDMs) were incubated with fluorescently labeled heat-shocked erythrocytes that externalized PtdSer ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…These specific genes function in efferocytosis and in the inhibition of cytokine responses (Axl), phagolysosome formation (Lamp1 and Cd63) and lipid efflux (Abcg1) (41,42). Clustering very closely were bin and TLR4 activation are critical initiators of the inflammatory response after ICH (30,(46)(47)(48)(49)(50)(51). After stimulation, bone marrowderived macrophages (BMDMs) were incubated with fluorescently labeled heat-shocked erythrocytes that externalized PtdSer ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…TLR/IL-1R, IL-17R, and TCR signaling may participate in this process (33)(34)(35)(36)(37). Our experiments mainly focused on TRAF6, which is downstream of inflammatory pathways, but the signaling that is initiated and mediated by TLRs/IL-1R, IL-17R, and the TCR requires further study.…”
Section: /2mentioning
confidence: 99%
“…Secondary brain injury following ICH includes hematoma toxicity, high metabolic injury, excitotoxicity, oxidative stress and inflammatory injury (1,(9)(10)(11). Previous studies into injury following ICH have focused downstream of inflammation and have not identified reagents that induce sufficient therapeutic effects in patients with ICH (5,8).…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLRs), which recognize distinct pathogen-and damage-associated molecular patterns, serve an important role in innate immunity and inflammatory responses (9,10). It has been demonstrated that TLR4 is involved in the inflammatory response that occurs following ICH, which subsequently activates nuclear factor (NF)-κB via the downstream myeloid differentiation primary response 88 (MyD88)/TIR-domain-containing adapter-inducing interferon-β (TRIF) signaling pathway (11). Some natural compounds, including Curcumin (12) and Vitamin D (13), attenuated TLR4-induced inflammation injury in atherosclerosis and hyperoxia-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%